PENGAMBILAN KEPUTUSAN WISATAWAN BERKUNJUNG DI NUSATENGGARA TIMUR MELALUI BAURAN PEMASARAN JASA PARIWISATA (Jurnal Ilmiah Pariwisata, 2013)
The study has two main problems, which are: (1) is there a significant relationship between the elements of people, product, price, place, promotion, positioning, physical, process, public relation, as marketing mix of tourism service to travelers visiting decision in East Nusa Tenggara? (2) which element of people, product, price, place, promotion, positioning, physical, process, and public relation of marketing mix elements of tourism services are the most dominant travelling decision of tourists to visit the province ? The study uses attitude scale questionnaire and regression and correlation as data analysis tools. The results showed that the multiple regression equation has the independent positive variables mean that independent variables were included as tourism marketing mix, worth to the model that determined the decision making. Answering the first problem with the significant results of simultaneous values of 0.000 below 0.05 means was that all the independent variables are very significant as the marketing mix affected the decision making (Y) in east nusa tenggara, while the answer of the second problem was the most dominant issue to determine traveling decision (Y) is the variable of promotion (0.003 < 0,05), variable of positioning (0.000 < 0.05), variable of physical (0.013 < 0.05), and variable of public (0.000 < 0.05).